2021
DOI: 10.1093/asj/sjab045
|View full text |Cite
|
Sign up to set email alerts
|

Defining Double Capsules: A Clinical and Histological Study

Abstract: Background Macrotextured breast implants are associated with double capsules. There is little agreement as to what defines double capsules, how they present, and whether different degrees of double capsule exist. Objectives This study aimed to define double capsules and report an association between double-capsule type and degree of tissue adherence. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Although double capsules have been reported in some patients before, 9,[14][15][16] this is the first known case of a patient with EDS with two independent implant capsules surrounding a single textured silicone implant. It seems likely that the two capsules resulted from the shearing of a single capsule at some point in the past, probably due to the COL5A genetic defect present in this patient's type I EDS.…”
Section: Discussionmentioning
confidence: 99%
“…Although double capsules have been reported in some patients before, 9,[14][15][16] this is the first known case of a patient with EDS with two independent implant capsules surrounding a single textured silicone implant. It seems likely that the two capsules resulted from the shearing of a single capsule at some point in the past, probably due to the COL5A genetic defect present in this patient's type I EDS.…”
Section: Discussionmentioning
confidence: 99%
“…A small study of Biocell-associated DCs has recently shown the inner lamina to range between a thin layer of nascent capsule and an identifiable organised one. Histological analysis revealed hypocellular fibrosis with synovial metaplasia and provided a clinicopathological correlation between DCs and failed tissue adherence [ 11 ].…”
Section: Discussionmentioning
confidence: 99%